Investigation of the influence of geometric parameters of a multi-nozzle jet pump on its energy characteristics. Issue 1 (March 2020) - Cheremushkin, V; Polyakov, A
Abstract: In this paper the optimization process of a jet pump developed according to a multi-nozzle scheme and designed to pump a mixture of water and soil is considered. Its flow part was designed, some measures were taken to accelerate the calculation process, including a method of setting the boundary conditions. Criteria and optimization parameters, the mathematical model used are given in the text. According to the calculation results, the best models and some dependencies of the criteria on the variated parameters are shown. The flow patterns in the flow part of the jet pump are presented.